Asymptomatic syringomatous adenoma of the nipple: A rare nipple neoplasm - Alex Suarez; Starr Mautner, MD; Michaela Ngyuen, MD; Katharine Lampen-Sachar, MD (Radiology Case Reports, 2022)
Syringomatous adenoma of the nipple is a very rare benign tumor, with radiographic and clinical characteristics that are difficult to differentiate from malignant tumors. Less than 60 cases have been identified thus far and most studies have not included radiographic findings. As such, the neoplasm requires more characterization within the literature. The usual clinical presentation of syringomatous adenoma of the nipple is symptomatic with a solitary, unilateral nipple mass within the subareolar region which may be tender and/or painful and may cause nipple inversion or discharge. We present a case of a 43-year-old woman that is unique, as the patient was asymptomatic and only presented following standard screening mammography. Moreover, we offer further characterization of the neoplasm through documented imaging and histologic findings.